Role of vitamin D, folic acid, ferritin, inflammation and oxidative stress in the pathogenesis of COVID-19 - Unsal, Velid; Sabancilar, Ilhan; Ozbek, Erdal; Mermutluoglu, Cigdem; Temiz, Hakan (Progress in Nutrition, 2022)
The COVID-19 pandemic is one of the most devastating and significant events of recent times. COVID-19 has so far become one of the worst infectious disease outbreaks of recent times, with more than 103 million cases and more than 2.2 million deaths. Viruses cause an explosion of inflammatory cytokines and reactive oxygen types. Oxidative stress is thought to have a key role in COVID-19. vitamin D, folic acid, calcium (Ca), magnesium (Mg) and ferritin levels are thought to be associated with COVID-19. The aim of this study is to investigate the role of oxidative stress, inflammation, vitamin D and folic acid, ferritin, Ca, Mg in the pathogenesis of COVID-19.45 patients diagnosed with COVID-19 and 45 healthy persons (control group) were included in the study. Vitamin D, ferritin, folic acid, CRP, Ca, Mg, Phosphorus were measured in an autoanalyzer, and SOD, GSH-Px and MDA were spectrophotometrically measured in the serum of the participants. TNF-α, IL-1β and IL6 levels were studied by ELISA method.The activity of SOD, GSH-px, antioxidant enzymes, Serum vitamin D, folic acid, Ca, Mg of the COVID-19 group was found to be significantly lower than the control group (p<0.05).Again, the levels of MDA, TNF-α, IL-1β, IL-6, CRP, ferritin in the Covid-19 group were found to be significantly higher than the control group (p<0.05).Antioxidant enzyme activities were low and oxidative stress was high in patients with COVID-19. At the same time, level of serum ferritin, CRP, TNF-α, IL-1β and IL6 were high, and level of Ca and Mg were low in patients with COVID-19.According to these results, we hypothesise think that the level of oxidative stress, inflammation, vitamin D, and serum ferritin, Ca, and Mg levels play a role in the pathogenesis of COVID-19. Future clinical trials should be conducted to further clarify the pathogenesis in patients with COVID-19.